The evaluation of the “Triple Jump” Method applied to students of Medical School - Cansanção, Isaac Farias; Fonseca, Diogo Vilar da; Matos, Bruno Mello de; Gois, William Novaes de; Martins, Thayze Teixeira Melo Nunes; Silva, Anekécia Lauro da; Nery, Joilda Silva; Lopes, Matheus Rodrigues; Morais, Natália Gomes de (Revista Eletrônica de Educação, 2017)
The present article aims to report an experience of tutors in performing a triple jump by evaluating the methodology of Problem-Based Learning (PBL) in a group of 37 students of the second period of a medical school of the Universidade Federal do Vale do São Francisco - UNIVASF, campus Paulo Afonso, Bahia, Brazil.The "triple jump" occurred in a daylight period, and was divided into three tutorial groups of nine students, a group of ten students and eight tutors. The problem situation was prepared by the tutors involved and all students were previously informed about the methodology applied. The assessment was divided into three stages (1-presentation of the problem; 2- individualized study; 3- Oral Presentation). In the end of the triple jump , it was applied an evaluative questionnaire and the 27 students had consented previously to fill them out. The students who participated in this application were able to quickly identify the learning objectives (94.6%). However, a small part of the participants (about 5%) suggested modifications on the time used to complete all the steps of the “Triple Jump”.The reported experience consolidate this evaluative tool has formative character and effective way in the measuring the teaching-learning process of students in health care in PBL methodby improving their educational background. Keywords: Higher education, Problem-Based Learning, Evaluation. References: BHUTIANI, M. et al. Triple-jump assessment model for use of evidence-based medicine. MedEdPORTAL Publications., v. 12, n. ID: 10373, 2016. BLAKE, J. M. et al. Introducing progress testing in McMaster University’s problem-based medical curriculum: psychometric properties and effect on learning. Acad Med, v. 71, n. 9, p. 1002-7, Sep 1996. BRASIL. Ministério da Educação. Conselho Nacional de Educação. Câmara de Educação Superior. Resolução nº 3, de 20 de junho de 2014. . Brasília (DF): Ministério da Educação; 2014. Institui Diretrizes Curriculares Nacionais do Curso de Graduação em Medicina e dá outras providências. Disponível em: <http://portal.mec.gov.br/ index.php?option=com_docman&view=download&alias=15874-rces003-14&category_slug =junho-2014-pdf&Itemid=30192 >. Acesso em: 11 de agosto de 2016. BRASIL. Ministério da Educação. Secretaria de Educação Superior. Diretrizes Curriculares para os Cursos de Graduação. Resolução CNE/ CES Nº 3, de 7 de novembro de 2001. Disponível em: < http://www.mec.gov.br/sesu/diretriz.htm >. Acesso em: 11 de agosto de 2016. CAPRA, F. O ponto da mutação: a ciência, a sociedade e a cultura emergente. Cultrix: São Paulo, 2006. ECHAVARRIA, M. V. Problem-based learning application in engineering. Revista EIA, p. 85-95, 2010. GONTIJO, E. D.; ALVIM, C. G.; LIMA, M. E. C. D. C. Manual de avaliação da aprendizagem no curso de graduação em Medicina. Rev. Docência Ens. Sup., v. 5, n. 1, p. 121, 2015. GRISI, S. J. F. E. A avaliação e o processo de formação do médico. Pediatria, São Paulo, v. 26, n. 4, p. 217-218, 2004. KOMATSU, R. S.; LIMA, V. V. Manual Famema 2003. Marília: Faculdade de Medicina de Marília, 2003. MITRE, S. M. et al. Metodologias ativas de ensino-aprendizagem na formação profissional em saúde: debates atuais. Ciênc Saúde Coletiva, v. 13, n. Suppl 2, p. S2133-44, 2008. PAINVIN, C. et al. The "triple jump" exercise - a structured measure of problem solving and self directed learning. Annu Conf Res Med Educ, v. 18, p. 73-7,1979. PINTO, A. S. S. et al. Inovação didática - Projeto de reflexão e aplicação de metodologias ativas de aprendizagem no ensino superior: uma experiência com “peer instruction”. Janus: Lorena, v. ano 6, n. 15, p. 75-87, 2012. POWLES, A. C. et al. The "triple-jump" exercise - further studies of an evaluative technique. Annu Conf Res Med Educ, v. 20, p. 74-9, 1981. RANGACHARI, P. K. The TRIPSE: A process-oriented evaluation for problem-based learning courses in basic sciences. Biochemistry and Molecular Biology Education, v. 30, n. 1, p. 57-60, 2002. SANTOS, C. P.; SOARES, S. R. Aprendizagem e relação professor-aluno na universidade: duas faces da mesma moeda. São Paulo: Est. Aval. Educ., v. 22, n. 49, p. 353-370, maio/ago 2011. SHIGUNOV NETO, A.; MACIEL, L. S. B. O ensino jesuítico no período colonial brasileiro: algumas discussões. Educar em Revista, p. 169-189, 2008. SMITH, R. M. The triple-jump examination as an assessment tool in the problem-based medical curriculum at the University of Hawaii. Acad Med, v. 68, n. 5, p. 366-72, May 1993. SORDI, M. R. L. Problematizando o papel da avaliação da aprendizagem nas metodologias inovadoras na área da saúde. Revista de Educação PUC-Campinas, v. 9, p. 52-61, 2000. TRONCON, L. Utilização de pacientes simulados no ensino e na avaliação de habilidades clínicas. Medicina Ribeirão Preto, v. 40, n. 2, p. 180-191, 2007. WATANABE, L. M. Manual de avaliação: curso de Medicina. Brasília: Fundação de Ensino e Pesquisa em Ciências da Saúde, 2002. 86p. XAVIER, L. N. et al. Analisando as metodologias ativas na formação dos profissionais de saúde: uma revisão integrativa. SANARE, v. 13, n. 1, p. 76-83, 2014.